2014
DOI: 10.1176/appi.ajp.2013.13010134
|View full text |Cite
|
Sign up to set email alerts
|

Association of Violence With Emergence of Persecutory Delusions in Untreated Schizophrenia

Abstract: The results indicate that the emergence of persecutory delusions in untreated schizophrenia explains violent behavior. Maintaining psychiatric treatment after release can substantially reduce violent recidivism among prisoners with schizophrenia. Better screening and treatment of prisoners is therefore essential to prevent violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(105 citation statements)
references
References 36 publications
5
98
0
2
Order By: Relevance
“…79 But in 1968, the second edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM) 80 recast paranoid schizophrenia as a condition of "hostility," "aggression," and projected anger, and included text explaining that, "the patient's attitude is frequently hostile and aggressive, and his behavior tends to be consistent with his delusions." 80(p34- 36) A somewhat similar story can be told about posttraumatic stress disorder (PTSD), another illness frequently associated with gun violence. 15 From the mid-19th century though World War II, military leaders and doctors assumed that combat-related stress afflicted neurotic or cowardly soldiers.…”
Section: Framing Health Mattersmentioning
confidence: 99%
See 1 more Smart Citation
“…79 But in 1968, the second edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM) 80 recast paranoid schizophrenia as a condition of "hostility," "aggression," and projected anger, and included text explaining that, "the patient's attitude is frequently hostile and aggressive, and his behavior tends to be consistent with his delusions." 80(p34- 36) A somewhat similar story can be told about posttraumatic stress disorder (PTSD), another illness frequently associated with gun violence. 15 From the mid-19th century though World War II, military leaders and doctors assumed that combat-related stress afflicted neurotic or cowardly soldiers.…”
Section: Framing Health Mattersmentioning
confidence: 99%
“…Writing in the American Journal of Psychiatry, Keers et al found that the emergence of "persecutory delusions" partially explained associations between untreated schizophrenia and violence. 36 At the same time, a number of seminal studies asserting links between violence and mental illness-including a 1990 study by Swanson et al 37 cited as fact by the New York Times in 2013 38 -have been critiqued for overstating connections between serious mental illness and violent acts. 39 Media reports often assume a binary distinction between mild and severe mental illness, and connect the latter form to unpredictability and lack of self-control.…”
Section: The Assumption That Mental Illness Causes Gun Violencementioning
confidence: 99%
“…The precise role of imagery in paranoid fears is yet to be determined [138, 139]. How paranoia affects social functioning [140, 141], what leads to acting on delusions [142], and what are the societal factors that increase paranoia [143] are important topics for future research. Much of our work has been inspired by listening to patients and trying out strategies during psychological therapy, as indicated in the personal accounts used throughout this review.…”
Section: Reasoningmentioning
confidence: 99%
“…Untreated schizophrenia was associated with the emergence of persecutory delusions at follow-up, which were associated with violence; therefore, maintaining psychiatric treatment after release can substantially reduce violent recidivism among prisoners with schizophrenia [Keers et al 2014].…”
Section: Forensic Implications Of Lai Apsmentioning
confidence: 99%